Preparation method, product and application of yttrium iron oxide loaded biochar composite material
By loading yttrium iron oxide on biochar and calcining to prepare composite materials, the problem of biochar's poor adsorption effect on chlormycin is solved, and efficient adsorption and magnetic properties are improved, while promoting the recycling of materials.
Patent Information
- Application Number
- CN202510130924.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The adsorption and removal effect of existing biochar materials on chlormycin in wastewater needs to be improved.
Biochar was prepared by using the oleracene fungi residue and calcining the supported yttrium iron oxide at high temperature under an inert atmosphere to prepare a yttrium iron oxide-supported biochar composite material with magnetic properties.
The adsorption activity and magnetic properties of the composite material are improved, so that it can efficiently adsorb chlormycin in wastewater and has good recycling performance.
Smart Images

Figure CN119608113A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biochar material preparation, and in particular to a preparation method, product and application of an yttrium iron oxide loaded biochar composite material. Background Art
[0002] Chlortetracycline (CTC) is one of the types of tetracycline antibiotics (TCs) residues in wastewater. It is widely used in the treatment of human diseases and animal husbandry due to its broad antibacterial spectrum, good efficacy, low cost and good safety. However, antibiotics cannot be completely absorbed or metabolized by organisms. Nearly 80% of antibiotics that cannot be metabolized will be excreted from the body in the form of active substances and eventually enter the ecological environment. The long-term presence of antibiotics in the environment may threaten human health through toxic effects. At the same time, the accumulation of discarded antibiotics from different sources in groundwater, surface water and wastewater will induce the evolution of antibiotic resistance genes, increasing the potential risk to the ecosystem. Therefore, it is very important and necessary to develop an efficient CTC treatment process.
[0003] Adsorption has become the first choice for treating chlortetracycline residues in wastewater due to its high efficiency, low cost and no toxic byproducts. Traditional adsorption materials mainly include activated carbon, biochar, metal oxides, graphene oxide materials, etc. The raw materials are widely available. For example, the raw materials of biochar are mostly agricultural products such as peanut shells, pepper straws, and potato peels. They are not only low-cost, but also can realize waste resource utilization. Biochar is a type of carbon-rich material with a highly developed pore structure, a loose and porous surface, a large specific surface area and a large number of organic functional groups. In recent years, it has been widely used in the field of environmental remediation due to its unique physical and chemical properties. In the environmental field, biochar can effectively remove various organic and inorganic pollutants, so it is widely used in the fixation and removal of pollutants in water and soil. At the same time, biochar also plays a role in reducing carbon emissions and mitigating climate change. However, the adsorption and removal effect of biochar materials on CTC in wastewater needs to be further improved. Summary of the invention
[0004] Based on the above content, the present invention provides a preparation method, product and application of a yttrium iron oxide loaded biochar composite material. The present invention uses oxytetracycline residue to prepare biochar, on which yttrium iron oxide is loaded, and calcined at high temperature under an inert atmosphere to prepare a composite material with obvious magnetic properties, which not only solves the problem of material recycling difficulties, but also promotes the recycling performance of the composite material.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is a method for preparing a yttrium iron oxide-loaded biochar composite material, comprising the following steps:
[0007] The fungus residue powder is soaked in a mixed acid solution, and then rinsed, dried, and calcined to obtain biochar;
[0008] Dissolving yttrium salt and iron salt in water to obtain a mixed salt solution;
[0009] dropping the mixed salt solution into boiling water and boiling the water to obtain a sol;
[0010] Adding an alkaline solution to the sol to cause precipitation and stirring, then adding the biochar, mixing, filtering, rinsing, and drying to obtain a solid;
[0011] calcining the solid to obtain the yttrium iron oxide-loaded biochar composite material;
[0012] The fungus residue powder is prepared by drying, crushing and grinding the oxytetracycline fungus residue.
[0013] The second technical solution of the present invention is a yttrium iron oxide loaded biochar composite material prepared according to the above-mentioned preparation method.
[0014] The third technical solution of the present invention is the application of the above-mentioned yttrium iron oxide loaded biochar composite material in the adsorption of chlortetracycline in wastewater.
[0015] The present invention discloses the following technical effects:
[0016] (1) The present invention loads yttrium ferrite on biochar material and calcines it at high temperature under an inert atmosphere to prepare a composite material with magnetic properties. Yttrium ferrite nanoparticles are loaded on the surface of a biochar material with a large specific surface area, and a composite material with certain characteristics is formed on the surface of the biochar by stacking the two. The pore structure and particle bridge formed after oxygen-free high-temperature calcination greatly increase the specific surface area of the adsorbent and the adsorption of CTC in wastewater.
[0017] (2) The method of the present invention uses biochar as a precursor and regulates the metal oxide loading. The iron oxide formed after calcination makes the catalyst magnetic. The functionalization treatment of biochar (i.e., the loading of metal oxides) enhances the adsorption activity of the overall adsorbent, making it magnetic, and modifies the surface charge properties of biochar to form more functional groups and a larger specific surface area, exposing more adsorption sites. Even at a low dosage, it can have a good adsorption effect, thereby achieving the purpose of efficiently adsorbing CTC in water.
[0018] (3) The yttrium iron oxide-loaded biochar composite material prepared by the method of the present invention has both excellent adsorption performance and high magnetism. Compared with the prior art, it improves the adsorption performance while also having recyclability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 X-ray diffraction spectra of the YFeO3 / BC composite materials prepared in Examples 1-2 of the present invention, BC prepared in Comparative Example 1, and YFeO3 prepared in Comparative Example 2;
[0021] Figure 2 This is the adsorption isotherm diagram of CTC by YFeO3 / BC-1:1 prepared in Example 1 of the present invention;
[0022] Figure 3 The adsorption amount of CTC by YFeO3 / BC-1:1 prepared in Example 1 of the present invention, BC prepared in Comparative Example 1, and YFeO3 prepared in Comparative Example 2;
[0023] Figure 4 The adsorption performance of the YFeO3 / BC composite material prepared in Example 1-2 of the present invention;
[0024] Figure 5 The recycling results of YFeO3 / BC-1:1 prepared in Example 1 of the present invention;
[0025] Figure 6 This is the TEM image of YFeO3 / BC-1:1 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] The "%" described in the present invention, unless otherwise specified, refers to mass percentage.
[0032] The first aspect of the present invention provides a method for preparing a yttrium iron oxide-loaded biochar composite material, comprising the following steps:
[0033] The fungus residue powder is soaked in a mixed acid solution, and then rinsed, dried, and calcined to obtain biochar;
[0034] Dissolving yttrium salt and iron salt in water to obtain a mixed salt solution;
[0035] dropping the mixed salt solution into boiling water and boiling the water to obtain a sol;
[0036] Adding an alkaline solution to the sol to cause precipitation and stirring, then adding the biochar, mixing, filtering, rinsing, and drying to obtain a solid;
[0037] calcining the solid to obtain the yttrium iron oxide-loaded biochar composite material;
[0038] The fungus residue powder is prepared by drying, crushing and grinding the oxytetracycline fungus residue.
[0039] The present invention has no particular limitation on the usage ratio of the mushroom residue powder and the mixed acid solution, and the usage of the mixed acid solution is sufficient to fully immerse the mushroom residue powder.
[0040] In a preferred embodiment of the present invention, the mixed acid solution is a mixed solution of HF and HCl; the mass fraction of HF in the mixed acid solution is 0.9% to 2.2%, and the mass fraction of HCl is 1.48% to 1.55%; the soaking time is 2 hours. The purpose of soaking is to remove organic components such as carbohydrates and proteins contained in the fungus residue.
[0041] In the present invention, the rinsing is performed three times with deionized water; and the flushing is performed with distilled water until it becomes neutral.
[0042] In a preferred embodiment of the present invention, when preparing biochar, the calcination temperature is 400° C. and the calcination time is 3 hours.
[0043] In a preferred embodiment of the present invention, the yttrium salt is Y(NO3)3·6H2O; the iron salt is Fe(NO3)3·9H2O; the concentration of the yttrium salt in the mixed salt solution is 0.15 mol / L; and the molar ratio of the yttrium salt to the iron salt is 1:1.
[0044] In the actual preparation process, the weighing ratio of yttrium salt to iron salt may be slightly different, and it is sufficient to ensure that the molar ratio of the two is approximately 1:1.
[0045] In a preferred embodiment of the present invention, the boiling time is 15 minutes; the alkaline solution is a K2CO3 solution with a mass concentration of 5%; the amount of the alkaline solution added is sufficient to make the phenolphthalein test paper turn red. In the present invention, the alkaline solution is added and the precipitation occurs, and the stirring is performed for 1 hour, and the purpose of stirring is to accelerate the precipitation of the obtained composite material.
[0046] In a preferred embodiment of the present invention, the amount of biochar added is 0.25 to 2 times the mass of yttrium ferrite generated by the yttrium salt and the iron salt.
[0047] In a preferred embodiment of the present invention, when the solid is calcined, the calcination conditions are: calcination at 700° C. for 3 hours under an inert atmosphere.
[0048] The second technical solution of the present invention is a yttrium iron oxide loaded biochar composite material prepared according to the above-mentioned preparation method.
[0049] The third technical solution of the present invention is the application of the above-mentioned yttrium iron oxide loaded biochar composite material in the adsorption of chlortetracycline in wastewater.
[0050] In a preferred embodiment of the present invention, the above-mentioned yttrium iron oxide-loaded biochar composite material is added to the wastewater; the addition amount of the yttrium iron oxide-loaded biochar composite material in the wastewater is 0.05 g / L; the concentration of chlortetracycline in the wastewater is 10-200 mg / L.
[0051] The adsorption experimental results of CTC show that the yttrium iron oxide loaded biochar composite material can effectively adsorb CTC and is an ideal material for a high-efficiency adsorbent.
[0052] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0053] The oxytetracycline residue used in the embodiments of the present invention comes from Inner Mongolia Autonomous Region, China.
[0054] The mass fraction of the HCl solution used in the embodiment of the present invention is 36% to 38%;
[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] Example 1
[0057] This embodiment provides a method for preparing a yttrium iron oxide-loaded biochar composite material (YFeO3 / BC-1:1), the steps are as follows:
[0058] S1: Dry the oxytetracycline residue, crush it, grind it and sieve it to obtain powder for later use.
[0059] S2: 44.65 mL of 55% HF solution and 80.71 mL of HCl solution were measured respectively, and the volume was fixed to 2 L. The treated fungus residue powder was weighed and added to the above solution to soak for 2 h. The mixture was rinsed three times with distilled water, dried, and calcined in a tubular furnace at 400 °C for 3 h to prepare biochar, which was recorded as BC.
[0060] S3: Symmetrically take 2.87g Y(NO3)3·6H2O and 3.03g Fe(NO3)3·9H2O and dissolve them in 50mL distilled water to prepare a mixed salt solution, and stir to fully dissolve it.
[0061] S4: Slowly drop the above solution into 500 mL of continuously boiling water and boil for 15 minutes. Stop boiling when a yellow-brown sol appears.
[0062] S5: Add 5% K2CO3 solution to the solution in step S4 until the phenolphthalein test paper turns red. After precipitation occurs, stir magnetically for 1 hour, add 1.4475g BC, stir evenly, cool to room temperature, filter, rinse with distilled water until pH≈7, and dry and grind to obtain a yellow-brown solid.
[0063] S6: The yellow-brown solid obtained in step S5 was calcined at 700°C for 3h in a tube furnace under a nitrogen atmosphere to obtain a YFeO3 / BC composite material, wherein the mass ratio of YFeO3 to BC is about 1:1, and is marked as YFeO3 / BC-1:1. Its X-ray diffraction spectrum is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared composite material has characteristic diffraction peaks of both YFeO3 and BC, which indicates the successful preparation of YFeO3 / BC.
[0064] Figure 2 The adsorption isotherm of CTC by YFeO3 / BC-1:1 prepared in Example 1; The relationship between the equilibrium adsorption amount and equilibrium concentration of CTC by YFeO3 / BC-1:1 is as follows: Figure 2 As shown. Figure 2 It can be seen that after adsorption equilibrium, the concentration of CTC decreased from the initial concentration of 10 mg / L, 30 mg / L, 50 mg / L, 75 mg / L, 100 mg / L, 150 mg / L, and 200 mg / L to 3.64 mg / L, 12.88 mg / L, 17.19 mg / L, 34.67 mg / L, 53.93 mg / L, 91.7 mg / L, and 130.77 mg / L, respectively. The adsorption amount of CTC by YFeO3 / BC-1:1 increases with the increase of initial concentration (10 mg / L to 200 mg / L). At low concentrations, the adsorption rate of CTC on YFeO3 / BC-1:1 is fast. As the concentration of CTC increases, the adsorption rate of CTC on YFeO3 / BC-1:1 slows down, and finally reaches the adsorption saturation point at a higher equilibrium adsorption value. The adsorption isotherm test process of CTC by YFeO3 / BC-1:1 is as follows: (at room temperature (25°C), placed in a glass bottle in a constant temperature oscillating box at 150rpm / min; take 200mL of prepared CTC solutions with different initial concentrations, add 10mg of adsorbent to the solution to start the reaction; after 48h of equilibrium, take 1mL of sample, filter through a 0.22μm filter to remove the adsorbent, and use a high performance liquid chromatograph for detection and analysis. The experimental conditions are: the initial concentrations of CTC are 10mg / L, 30mg / L, 50mg / L, 75mg / L, 100mg / L, 150mg / L, and 200mg / L, the solid-liquid ratio is 0.05g / L, and the pH is 6).
[0065] Comparative Example 1
[0066] In this comparative example, the fungus residue biochar was prepared as a control catalyst by high temperature calcination, and the steps are as follows:
[0067] S1: drying the oxytetracycline residue, crushing and grinding it, and then sieving it to obtain a powder for later use;
[0068] S2: 44.65 mL HF and 80.71 mL HCl solutions were measured respectively, and the volume was fixed to 2 L. The treated fungus residue powder was weighed and added to the above solution to soak for 2 h. The mixture was rinsed three times with distilled water, dried, and calcined in a tubular furnace at 400 °C for 3 h to prepare biochar, which was recorded as BC.
[0069] Comparative Example 2
[0070] This comparative example provides a chlortetracycline adsorbed by yttrium ferrite, and the preparation method is as follows:
[0071] Weigh 2.87g Y(NO3)3·6H2O and 3.03g Fe(NO3)3·9H2O and dissolve them in 50mL distilled water, slowly drip into 500mL boiling water, boil for 15min, stop boiling after a yellow-brown sol appears. Add 5% K2CO3 solution to the solution until the phenolphthalein test paper turns red, stir magnetically for 1h after precipitation appears, cool to room temperature, filter, rinse with distilled water until neutral, dry and grind to obtain a yellow-brown solid, calcine at 700℃ for 3h in a tube furnace under nitrogen atmosphere to obtain YFeO3 material.
[0072] The adsorption effects of YFeO3 / BC-1:1, BC and YFeO3 prepared in Example 1 and Comparative Example 1 and Comparative Example 2 on chlortetracycline in wastewater as adsorption materials were tested as follows:
[0073] The experiment was carried out at room temperature (25°C) in a glass bottle placed in a constant temperature shaking box at 150 rpm / min.
[0074] Take 200 mL of the prepared CTC solution and add 10 mg of adsorbent to the solution to start the reaction;
[0075] After 48 h of equilibrium, 1 mL of the sample was taken, filtered through a 0.22 μm filter to remove the adsorbent, and analyzed using a high performance liquid chromatograph.
[0076] The experimental conditions were: CTC initial concentration was 50 mg / L, solid-liquid ratio was 0.05 g / L, and pH was 6.
[0077] The results are as follows Figure 3 As shown by Figure 3It can be seen that the equilibrium adsorption capacity of CTC by BC in Comparative Example 1 is only 7.62 mg / g, the equilibrium adsorption capacity of CTC by YFeO3 adsorbent in Comparative Example 2 is 64.05 mg / g, and the equilibrium adsorption capacity of CTC by YFeO3 / BC-1:1 in Example 1 can reach 355.49 mg / g. Compared with single BC or YFeO3, the adsorption performance of YFeO3 / BC-1:1 prepared by combining BC and YFeO3 has been greatly improved, indicating that the YFeO3 / BC composite material can adsorb CTC more efficiently, and the yttrium ferrite loading changes the physical and chemical properties of biochar and improves the adsorption performance of pollutants.
[0078] Example 2
[0079] This example explores the effect of different mass ratios of yttrium ferrite (YFeO3) / biochar (BC) on the adsorption performance of YFeO3 / BC composite materials. The preparation method of YFeO3 / BC composite materials with different mass ratios of yttrium ferrite (YFeO3) / biochar (BC) is as follows:
[0080] The only difference from Example 1 is that the amount of BC added in step S5 is adjusted so that the mass ratio of YFeO3 and BC in the YFeO3 / BC composite material is approximately 2:1, 4:1, 9:1, and 1:2. The prepared YFeO3 / BC composite materials are correspondingly marked as YFeO3 / BC-2:1, YFeO3 / BC-4:1, YFeO3 / BC-9:1, and YFeO3 / BC-1:2.
[0081] YFeO3 / BC-2:1, YFeO3 / BC-4:1, YFeO3 / BC-9:1 and YFeO3 / BC-1:2 prepared in Example 2 were used as adsorption materials to test their adsorption effect on chloramphenicol in wastewater, and the testing method was the same as that in Example 1.
[0082] The results are as follows Figure 4 As shown, when the mass ratio of YFeO3 and BC is different, under the same experimental conditions, different adsorption effects are shown in the process of adsorbing CTC. The adsorption amount of TC by YFeO3 / BC-1:1 can reach 355.49 mg / g, indicating that the composite material has efficient chlortetracycline adsorption performance.
[0083] Compared with biochar catalyst, the present invention uses oxytetracycline residue to prepare biochar, and on this basis loads yttrium iron oxide to prepare YFeO3 / BC composite material, which not only solves the resource utilization of oxytetracycline residue waste, but also realizes the reuse of yttrium elements in wastewater discharged from industries such as ceramics, which not only reduces the preparation cost, but also reduces the potential threat to the environment. Figure 5As shown, the adsorption amount of YFeO3 / BC-1:1 prepared in Example 1 is still 84.97% of the initial amount after three cycles, and it still has good adsorption capacity and high stability.
[0084] like Figure 6 As shown, the yttrium iron oxide particles in the composite material are dispersed on the surface of biochar and stacked on each other to form pores of different sizes, which increases the specific surface area, exposes more adsorption sites, and further improves the adsorption capacity of the composite material.
[0085] The present invention loads yttrium ferrite on biochar material, yttrium ferrite particles are highly dispersed on the surface of biochar, and calcined in a high-temperature inert environment to prepare a composite material with magnetic properties. The particles of the composite material formed after oxygen-free high-temperature calcination are nanometer-level, with the advantages of small particles, high dispersion, large specific surface area, etc. At the same time, the particles are stacked on each other, which improves the pore structure and stability of the adsorbent and improves the adsorption performance.
[0086] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a yttrium iron oxide-loaded biochar composite material, characterized in that: The following steps are involved: The fungus residue powder is soaked in a mixed acid solution, and then rinsed, dried, and calcined to obtain biochar; Dissolving yttrium salt and iron salt in water to obtain a mixed salt solution; dropping the mixed salt solution into boiling water and boiling the water to obtain a sol; Adding an alkaline solution to the sol to cause precipitation and stirring, then adding the biochar, mixing, filtering, rinsing, and drying to obtain a solid; calcining the solid to obtain the yttrium iron oxide-loaded biochar composite material; The fungus residue powder is prepared by drying, crushing and grinding the oxytetracycline fungus residue.
2. The preparation method according to claim 1, characterized in that: The mixed acid solution is a mixed solution of HF and HCl; the mass fraction of HF in the mixed acid solution is 0.9% to 2.2%, and the mass fraction of HCl is 1.48% to 1.55%; and the immersion time is 2 hours.
3. The preparation method according to claim 1, characterized in that: When preparing biochar, the calcination temperature is 400° C. and the calcination time is 3 hours.
4. The preparation method according to claim 1, characterized in that: The yttrium salt is Y(NO3)3·6H2O; the iron salt is Fe(NO3)3·9H2O; the concentration of the yttrium salt in the mixed salt solution is 0.15 mol / L; the molar ratio of the yttrium salt to the iron salt is 1:
1.
5. The preparation method according to claim 1, characterized in that: The boiling time is 15 minutes; the alkaline solution is a K2CO3 solution with a mass concentration of 5%; the amount of the alkaline solution added is sufficient to make the phenolphthalein test paper turn red.
6. The preparation method according to claim 1, characterized in that: The amount of biochar added is 0.25 to 2 times the mass of yttrium ferrite generated by yttrium salt and iron salt.
7. The preparation method according to claim 1, characterized in that: When the solid is calcined, the calcination conditions are: calcination at 700° C. for 3 hours under an inert atmosphere.
8. The yttrium iron oxide-loaded biochar composite material prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the yttrium iron oxide-loaded biochar composite material as claimed in claim 8 in the adsorption of chlortetracycline in wastewater.
10. The use according to claim 9, characterized in that: The yttrium iron oxide loaded biochar composite material according to claim 8 is added to the wastewater; the addition amount of the yttrium iron oxide loaded biochar composite material in the wastewater is 0.05 g / L; the concentration of chlortetracycline in the wastewater is 10-200 mg / L.
Citation Information
Patent Citations
Method for preparing yttrium ferrite nanometer powder by using microwaves
CN102173459A
Method for preparing modified biochar through ferrate oxidation under alkaline condition
CN105289485A
Preparation method of sandwich-structure magnetic mesoporous imprinted material capable of separating holmium, erbium, thulium, ytterbium, lutecium or yttrium
CN106824127A
Ferromagnetic carbon-based composite material, and preparation method and application thereof
CN113680322A
Adsorbent as well as preparation method and application thereof
CN113731363A
Cited By
Method for treating thallium-containing wastewater by using biochar doped with metal oxide
CN121292571A